2023
DOI: 10.5603/cj.a2021.0085
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic markers of cardiac amyloidosis in patients with heart failure and left ventricular hypertrophy

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…is provided in Table 1 8–25,34–77 . A graphical representation of the prevalence of cardiac amyloidosis across various populations subgroups is provided in Figure (and online supplementary Figure – focused version).…”
Section: Resultsmentioning
confidence: 99%
“…is provided in Table 1 8–25,34–77 . A graphical representation of the prevalence of cardiac amyloidosis across various populations subgroups is provided in Figure (and online supplementary Figure – focused version).…”
Section: Resultsmentioning
confidence: 99%
“…LV hypertrophy (LVH) is CA patients’ most common echocardiographic finding (Fig. 3 A) [ 10 ]. It was reported that with the help of gene detection, nearly 5% of the patients initially diagnosed with hypertrophic cardiomyopathies were eventually diagnosed as ATTRm [ 11 ].…”
Section: Conventional Echocardiographic Findings Of Camentioning
confidence: 99%